Short and Long Term Repeatability of Saccharin Transit Time in Current, Former, and Never Smokers - Emma, Rosalia; Caponnetto, Pasquale; Cibella, Fabio; Caruso, Massimo; Conte, Gianluca; Benfatto, Francesca; Ferlito, Salvatore; Gulino, Alessandro; Polosa, Riccardo (Frontiers in Physiology, 2020)
Smoking progressively damages the efficiency of mucociliary clearance (MCC) defense mechanisms, thus contributing to increased susceptibility to respiratory infections. Prolonged mucociliary clearance transit time (MCCTT) caused by chronic smoking has been investigated by saccharin test, but little data is available about its short- and long-term reproducibility. Moreover, it is not known if MCC impairment can be reversed when stopping smoking. Objective of the study is to investigate and compare short (3 days) and long term (30 days) repeatability of baseline saccharin transit time (STT) among current, former, and never smokers. STT results were analyzed in 39 current, 40 former, and 40 never smokers. Significant (p < 0.0001) short-term and long-term repeatability of STT were observed in current (R squared = 0.398 and 0.672, for short- and long-term, respectively) and former smokers (R squared = 0.714 and 0.595, for short- and long-term, respectively). Significant differences in MCCTT were observed among the three study groups (p < 0.0001); the median (IQR) MCCTT being 13.15 (10.24–17.25), 7.26 (6.18–9.17), and 7.24 (5.73–8.73) minutes for current, former and never smokers, respectively. Comparison between current smokers and former smokers was significantly different (p < 0.0001). There was no significant difference between former and never smokers. The Saccharin test was well tolerated by all participants. We have shown for the first time high level repeatability in both current and former smokers. Moreover, MCC impairment can be completely reversed, former smokers exhibiting similar STT as never smokers. Measurement of STT is a sensitive biomarker of physiological effect for the detection of early respiratory health changes and may be useful for clinical research.